The negative impact of vegetarian and vegan labels: Results from randomized controlled experiments with US consumers - Berke, Alex; Larson, Kent (Appetite, 2023)
Reducing consumption of animal products is a critically important challenge in efforts to mitigate the climate crisis. Despite this, meals containing animal products are often presented as the default versus more environmentally sustainable vegetarian or vegan options. We tested whether vegetarian and vegan labels on menu items negatively impact the likelihood of US consumers choosing these items by using a between-subjects experimental design, where participants chose a preference between two items. Menu items were presented with titles and descriptions typical at restaurants, and a random group saw "vegan" or "vegetarian" labels in the titles of one of the two items. Two field studies were conducted at a US academic institution, where people selected what to eat via event registration forms. The methodology was extended to an online study, where US consumers selected what to hypothetically eat in a series of choice questions. Overall, results showed the menu items were significantly less likely to be chosen when they were labeled, with much larger effects in the field studies, where choice was not hypothetical. In addition, the online study showed male participants had a significantly higher preference for options containing meat versus other participants. Results did not indicate the impact of labels differed by gender. Furthermore, this study did not find that vegetarians and vegans were more likely to choose items with meat when the labels were removed, indicating that removing labels did not negatively impact them. The results suggest removing vegetarian and vegan labels from menus could help guide US consumers towards reduced consumption of animal products.